Heterometallic CuIIFeIII and CuIIMnIII alkoxo-bridged complexes revealing a rare hexanuclear M6(μ-X)7(μ3-X)2 molecular core. Issue 32 (18th July 2018) - Nesterova, Oksana V.; Nesterov, Dmytro S.; Vranovičová, Beáta; Boča, Roman; Pombeiro, Armando J. L.
Abstract : The uncommon cores of Cu/M (M = Fe, Mn) diethanolamine-based complexes as well as the magnetic and catalytic studies of the copper/iron one are discussed. Abstract : The novel hexanuclear complexes [Cu4 Fe2 (OH)(Piv)4 ( t BuDea)4 Cl]·0.5CH3 CN (1 ) and [Cu4 Mn2 (OH)(Piv)4 ( t BuDea)4 Cl] (2 ) were prepared through one-pot self-assembly reactions of copper powder and iron(ii ) or manganese(ii ) chloride with N-tert -butyldiethanolamine (H2 t BuDea) and pivalic acid (HPiv) in acetonitrile. Crystallographic studies revealed the uncommon molecular core type M6 (μ-X)7 (μ3 -X)2 in1 and2, which can be viewed as a combination of two trimetallic M3 (μ-X)2 (μ3 -X) fragments joined by three bridging atoms. The analysis and classification of the hexanuclear complexes having a M3 (μ-X)2 (μ3 -X) moiety as a core forming fragment using data from the Cambridge Structural Database (CSD) were performed. Variable-temperature (1.8–300 K) magnetic susceptibility measurements of1 showed a decrease of the effective magnetic moment value at low temperature, indicative of antiferromagnetic coupling between the magnetic centres ( J Fe–Cu / hc = −6.9 cm −1, J Cu–Cu / hc = −4.1 cm −1, J Fe–Fe / hc = −24.2 cm −1 ). Complex1 acts as a catalyst in the reaction of mild oxidation of cyclohexane with H2 O2, showing the yields of products, cyclohexanol and cyclohexanone, up to 17% using pyrazinecarboxylic acid as a promoter. In the oxidation of cis -1, 2-dimethylcyclohexane with m -chloroperoxybenzoic acid ( m -CPBA), 70% of retention of stereoconfiguration was observed for tertiary alcohols. Compound1 also catalyses the amidation of cyclohexane with benzamide. In all three catalytic reactions the by-products were investigated in detail and discussed.